Developing a middle-range theory to explain how cash transfers work to tackle the social determinants of health: A realist case study. (June 2020) - Owusu-Addo, Ebenezer; Renzaho, Andre M.N.; Smith, Ben J.
Highlights: For CTs to have greater impact on the SDoH, there is a need for intersectoral collaboration. CTs require community engagement, and beneficiary education to function effectively. Beneficiaries' voice in program decision-making is key CT mechanism of change. The psychological context of decision-making in extreme poverty needs attention in CT design and implementation. Abstract: Cash transfers (CTs) are increasingly high on the agenda of most governments and development partners in low-and middle-income countries. Even though burgeoning evidence points to CTs' impact on the social determinants of health (SDoH), there is little evidence about how and why CTs work to influence the SDoH. This paper reports on a realist evaluation aimed at developing a middle-range theory that explains how CTs influence the SDoH by exploring program mechanisms of change and associated contextual factors. Qualitative interviewing was employed including key informant interviews (N = 36), in-depth-interviews (N = 32) and focus groups with program beneficiaries (N = 12), and observations. The study found that at the meso level, key mechanisms of collaboration and inter-sectoral working, formalisation of roles of service providers, and a shared vision across sectors were important to both the implementation and outcomes of CTs. Contextual factors that influenced program mechanisms at the meso level include active involvement of sector ministries and their decentralised departments in program policy formulation and design, availability of resources, and availability of a single registry containing information on program beneficiaries. At the micro level, program mechanisms of change identified include household empowerment, needs prioritisation and choice making, risk taking behaviour, program awareness, and beneficiaries' voice in program decision-making and implementation. Contextual factors that influence the micro mechanisms are categorised into structural factors (e.g. community/beneficiaries' involvement in decision-making), geographical factors (e.g. availability and access to quality services), community factors (e.g. availability of market and economic opportunities), and individual level factors (e.g. psychological context of poverty and child motivation). This realist evaluation provides evidence-based understandings regarding CTs mechanism of change in the contexts within which they operate, and can inform CT policy, design, implementation, adaptation and future evaluation.